Chemical composition of Heracleum sosnowskyi (Manden.) root essential oil and phytotoxicity of its nanoemulsions on radish seedlings - Grace Azeez; Anna Wajs-Bonikowska; Anna Łętocha; Magdalena Rys; Roshni Naushad; Paula Andrade Rodriguez; Małgorzata Miastkowska; Agnieszka Synowiec (Phytochemistry Letters, 2026)

Mu or delta opioid receptor antagonists increase the expression of social conditioned place preference in early adolescent mice - Zofia Harda; Marta Klimczak; Klaudia Misiołek; Magdalena Chrószcz; Aleksandra Rzeszut; Łukasz Szumiec; Maria Kaczmarczyk-Jarosz; Rafał Ryguła; Barbara Ziółkowska; Jan Rodriguez Parkitna (Psychopharmacology, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Enhancing Community Pharmacists’ Professional Competencies and Sun-Safe Behaviors Through the FarmaSoludable Educational Program - Guillermo J. Pozuelo-Sánchez; Magdalena de Troya-Martín; Francisco Rivas Ruiz; Alba Rodriguez-Martinez; Andras Subert; Maria Alvarez de Sotomayor (Journal of Cancer Education, 2026)
This study examined the impact of a structured educational intervention on professional competencies in individualized photoprotection counselling and on personal sun-safe behaviors. A quasi-experimental pre–post study was conducted among community pharmacists in Seville, Spain, in 2024. The intervention consisted of a blended educational program comprising an online training course delivered by a multidisciplinary faculty and a one-day practical session. Professional counselling practices were assessed using the Counselling Habits in Individualized Photoprotection questionnaire, while personal habits, attitudes, and knowledge related to photoprotection were evaluated using the Habits, Attitudes, and Knowledge in Photoprotection questionnaire. Data were collected at baseline and after completion of the intervention, and analyses included descriptive and comparative pre–post statistics, with statistical significance set at p < 0.05. A total of 116 pharmacists completed the baseline professional assessment and 80 the post-intervention, while 125 and 85 pharmacists completed the personal behavior questionnaire, respectively. Professional competencies improved significantly, including identification of skin cancer risk factors (45.2% to 72.2%), promotion of skin self-examination (31.6% to 65.8%), and adaptation of counselling to occupational sun exposure ( p < 0.001). Knowledge scores increased from 6.03 to 7.07 ( p < 0.001). Personal sun-safe behaviors also improved, including sunscreen use, regular reapplication, and reduced sunburn frequency. Knowledge of early skin cancer detection criteria increased markedly (ABCDE rule: 61.5% to 100%; ugly duckling sign: 27.9% to 98.8%; p < 0.001). The FarmaSoludable educational program improved professional competencies and personal preventive behaviors, supporting pharmacists’ roles as behavioral role models and educators for community knowledge transfer.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Continental Contrasts in Climate Extremes That Control Tree Fecundity - James S. Clark; Robert Andrus; Margarita Arianoutsou; Davide Ascoli; Yves Bergeron; Michal Bogdziewicz; Thomas Boivin; Raul Bonal; Thomas Caignard; Maxime Cailleret; Rafael Calama; J. Julio Camarero; et al. (Global Change Biology, 2026)
In 2023, more than half of olive harvests ( Olea europaea ) across Spain, Greece, and Türkiye were lost to drought. The same year late freeze destroyed 90% of the peach crop ( Prunus persica ) on the Georgia Piedmont and the apple crop ( Malus domestica ) in central New York, Vermont, and southern Quebec. Climate extremes now rank with the costliest threats to agriculture, but their role in forest recovery from diebacks that are happening globally is unknown for lack of tree fecundity estimates in forests. Tolerance of climate extremes could depend on past exposure but constrained by phylogenetic conservatism. We report a continental scale analysis of climate extremes and forest fecundity across North America and Europe showing that responses to late freeze and drought are happening now. Species differences are not explained by the traits typically included in ecological studies and they are weakly associated with phylogeny. Late freeze, that is, freezing temperatures that follow the onset of flower development in spring, is shown to be “normal” in North America, but not Europe, potentially explaining failed seed production due to delayed onset and the resultant shorter growing period by North American transplants dating back at least to the 18th century. Drought has thus far had the greatest impacts in dry forested regions, but here too, species differences are not explained by traditional trait values. If responses have been buffered from drought and late freeze by past exposure, acclimation and local adaptation prove inadequate as extremes intensify.

L-DOPA Induces Spatially Discrete Changes in Gene Expression in the Forebrain of Mice with a Progressive Loss of Dopaminergic Neurons - Anna Radlicka-Borysewska; Magdalena Ziemiańska; Mateusz Zięba; Łukasz Szumiec; Monika Bagińska; Magdalena Chrószcz; Sławomir Gołda; Jacek Hajto; Michał Korostyński; Grzegorz Kreiner; Joanna Pera; Marcin Piechota; et al. (Molecular Neurobiology, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

New palynological record for the Puesto Albornoz Formation (Golfo San Jorge basin, Argentina): Stratigraphic and paleoenvironmental implications - Valeria S. Perez Loinaze; Magdalena Llorens; Agustín R. Rodriguez; José O. Allard; Nicolás Foix (Journal of South American Earth Sciences, 2024)

Interlaboratory study: Testing reproducibility of solid biofuels component identification using reflected light microscopy - Agnieszka Drobniak; Maria Mastalerz; Zbigniew Jelonek; Iwona Jelonek; Tushar Adsul; Neža Malenšek Andolšek; Omid Haeri Ardakani; Tara Congo; Batbold Demberelsuren; Bryon S. Donohoe; Ashley Douds; Deolinda Flores; et al. (International Journal of Coal Geology, 2023)

Regulatory mechanisms behind the phenotypic plasticity associated with Setaria italica water deficit tolerance - Vanessa Fuentes Suguiyama; Jae Diana Paredes Rodriguez; Tatiane Cristina Nicomedio dos Santos; Bruno Silvestre Lira; Luis Alejandro de Haro; João Paulo Naldi Silva; Eduardo Leite Borba; Eduardo Purgatto; Emerson Alves da Silva; Nicolas Bellora; Fernando Carrari; Danilo da Cruz Centeno; et al. (Plant Molecular Biology, 2022)

Sun Protection Policies and Practices in Preschool and Elementary Schools in Andalusia (Spain) - Cristina García-Harana; María Victoria de Gálvez Aranda; Nuria Blazquez-Sanchez; Francisco Rivas-Ruiz; A. Rodriguez-Martinez; Magdalena de Troya-Martín (Journal of Cancer Education, 2022)

Globally, tree fecundity exceeds productivity gradients - Valentin Journé; Robert Andrus; Marie‐Claire Aravena; Davide Ascoli; Roberta Berretti; Daniel Berveiller; Michal Bogdziewicz; Thomas Boivin; Raul Bonal; Thomas Caignard; Rafael Calama; Jesús Julio Camarero; et al. (Ecology Letters, 2022)
Lack of tree fecundity data across climatic gradients precludes the analysis of how seed supply contributes to global variation in forest regeneration and biotic interactions responsible for biodiversity. A global synthesis of raw seedproduction data shows a 250‐fold increase in seed abundance from cold‐dry to warm‐wet climates, driven primarily by a 100‐fold increase in seed production for a given tree size. The modest (threefold) increase in forest productivity across the same climate gradient cannot explain the magnitudes of these trends. The increase in seeds per tree can arise from adaptive evolution driven by intense species interactions or from the direct effects of a warm, moist climate on tree fecundity. Either way, the massive differences in seed supply ramify through food webs potentially explaining a disproportionate role for species interactions in the wet tropics.

Conservation Policy Changes in Protected Areas on Hilltops in Brazil: Effects on Hydrological Response in a Small Watershed - Ulises Rodrigo Magdalena; Cristiane Nunes Francisco; Lucas Garofolo Lopes; Daniel Andrés Rodriguez (Water Resources Management, 2022)

Lithospheric density structure of the southern Central Andes constrained by 3D data-integrative gravity modelling - Constanza Rodriguez Piceda; Magdalena Scheck Wenderoth; Maria Laura Gomez Dacal; Judith Bott; Claudia Beatriz Prezzi; Manfred R. Strecker (International Journal of Earth Sciences, 2021)
The southern Central Andes (SCA) (between 27° S and 40° S) is bordered to the west by the convergent margin between the continental South American Plate and the oceanic Nazca Plate. The subduction angle along this margin is variable, as is the deformation of the upper plate. Between 33° S and 35° S, the subduction angle of the Nazca plate increases from sub-horizontal (< 5°) in the north to relatively steep (~ 30°) in the south. The SCA contain inherited lithological and structural heterogeneities within the crust that have been reactivated and overprinted since the onset of subduction and associated Cenozoic deformation within the Andean orogen. The distribution of the deformation within the SCA has often been attributed to the variations in the subduction angle and the reactivation of these inherited heterogeneities. However, the possible influence that the thickness and composition of the continental crust have had on both short-term and long-term deformation of the SCA is yet to be thoroughly investigated. For our investigations, we have derived density distributions and thicknesses for various layers that make up the lithosphere and evaluated their relationships with tectonic events that occurred over the history of the Andean orogeny and, in particular, investigated the short- and long-term nature of the present-day deformation processes. We established a 3D model of lithosphere beneath the orogen and its foreland (29° S–39° S) that is consistent with currently available geological and geophysical data, including the gravity data. The modelled crustal configuration and density distribution reveal spatial relationships with different tectonic domains: the crystalline crust in the orogen (the magmatic arc and the main orogenic wedge) is thicker (~ 55 km) and less dense (~ 2900 kg/m 3 ) than in the forearc (~ 35 km, ~ 2975 kg/m 3 ) and foreland (~ 30 km, ~ 3000 kg/m 3 ). Crustal thickening in the orogen probably occurred as a result of stacking of low-density domains, while density and thickness variations beneath the forearc and foreland most likely reflect differences in the tectonic evolution of each area following crustal accretion. No clear spatial relationship exists between the density distribution within the lithosphere and previously proposed boundaries of crustal terranes accreted during the early Paleozoic. Areas with ongoing deformation show a spatial correlation with those areas that have the highest topographic gradients and where there are abrupt changes in the average crustal-density contrast. This suggests that the short-term deformation within the interior of the Andean orogen and its foreland is fundamentally influenced by the crustal composition and the relative thickness of different crustal layers. A thicker, denser, and potentially stronger lithosphere beneath the northern part of the SCA foreland is interpreted to have favoured a strong coupling between the Nazca and South American plates, facilitating the development of a sub-horizontal slab.

Multi-Tissue Methylation Clocks for Age and Sex Estimation in the Common Bottlenose Dolphin - Todd R. Robeck; Zhe Fei; Amin Haghani; Joseph A. Zoller; Caesar Z. Li; Karen J. Steinman; Stacy Dirocco; Lydia Staggs; Todd Schmitt; Steve Osborn; Gisele Montano; Magdalena Rodriguez; et al. (Frontiers in Marine Science, 2021)
Accurate identification of individual ages within wild bottlenose dolphins ( Tursiops truncatus ) is critical for determining population health and the development of population management strategies. As such, we analyzed DNA methylation (DNAm) patterns by applying a custom methylation array (HorvathMammalMethyl40) to both blood ( n = 140) and skin samples ( n = 87) from known age or approximate age (0–57 years) bottlenose dolphins. We present three bottlenose dolphin specific age estimation clocks using combined blood and skin [48 CpGs, R = 0.93, median absolute error (MAE) = 2.13 years], blood only (64 CpGs, R = 0.97, error = 1.46 years) and skin only (39 CpGs, R = 0.95, error = 2.53). We characterized individual cytosines that correlate with sex and age in dolphins and developed a sex estimator based on 71 CpGs that predicts the sex of any odontocete species with 99.5% accuracy. The presented epigenetic clocks are expected to be useful for conservation efforts and for determining if anthropogenic events affect aging rates in wild populations.

The functional connectivity in the motor loop of human basal ganglia - Clara Rodriguez-Sabate; Magdalena Sabate; Catalina Llanos; Ingrid Morales; Alberto Sanchez; Manuel Rodriguez (Brain Imaging and Behavior, 2017)

Diffusional conductances to CO2 as a target for increasing photosynthesis and photosynthetic water-use efficiency - Jaume Flexas; Ülo Niinemets; Alexander Gallé; Margaret M. Barbour; Mauro Centritto; Antonio Diaz-Espejo; Cyril Douthe; Jeroni Galmés; Miquel Ribas-Carbo; Pedro L. Rodriguez; Francesc Rosselló; Raju Soolanayakanahally; et al. (Photosynthesis Research, 2013)

Characterization of CCDC28B reveals its role in ciliogenesis and provides insight to understand its modifier effect on Bardet–Biedl syndrome - Magdalena Cardenas-Rodriguez; Daniel P. S. Osborn; Florencia Irigoín; Martín Graña; Héctor Romero; Philip L. Beales; Jose L. Badano (Human Genetics, 2013)

Assessment of storage protein variation in relation to some morphological characters in a sample of Spanish landraces of common wheat (Triticum aestivum L. ssp. aestivum) - Magdalena Ruiz; E.V. Metakovsky; M. Rodriguez-Quijano; J.F. Vazquez; J.M. Carrillo (Genetic Resources and Crop Evolution, 2002)